A process approach to improving pain management in the emergency department: development and evaluation. Issue 3 (1st May 2000) - Kelly, Anne-Maree
Abstract : Aim —(1) To describe a process approach to the improvement of pain management in emergency departments. (2) To compare analgesia ordering and administration practices for patients with acute fractures before and after implementation of a nurse managed, titrated intravenous narcotic policy. Method —Retrospective chart review of patients with long bone fractures for the years 1993 and 1997. Results —There was a dramatic change in analgesia administration practices away from the intramuscular route in favour of the intravenous route (p<0.001). For long bone fractures, in 1993, 53% of patients received intramuscular narcotic analgesia compared with 5% in 1997. In contrast, in 1993, 6% of the patients received intravenous narcotic analgesia compared with 54% in 1997. Conclusion —This study demonstrates that a process approach to improving pain management that resulted in both changes in drug administration and pain assessment and management processes made a significant and sustained change to analgesia ordering and administration practices for patients with long bone fractures in an emergency department.